2014
DOI: 10.1038/leu.2014.169
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of DOT1L in leukemia and normal development

Abstract: Methylation of lysines within histone proteins represents a posttranslational modification system that can have profound effects on gene expression. An evolutionarily conserved, but poorly understood, histone methylation mark occurs on lysine 79 on histone H3 (H3K79). The H3K79 methyltransferase, DOT1L, is involved in a number of key processes ranging from gene expression to DNA-damage response and cell cycle progression. Recently, DOT1L has also been implicated in the development of mixed lineage leukemia (ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 66 publications
(123 reference statements)
1
82
0
Order By: Relevance
“…Although the effects of inhibition of BRD4 and DOT1L have generally been best characterized in the MLL-FP leukemias, emerging evidence suggests that therapies against these targets may play a role in other molecular subsets of acute leukemia and indeed other malignancies [46][47][48][49] . The differential sensitivity to these therapies in other cancers is presumably the result of intrinsic differences in the molecular pathogenesis of these diseases as well as the existence of several other protein complexes that lack DOT1L or BRD4 and affect or regulate malignant transcription programs initiated by non-MLL-FP oncogenes 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of inhibition of BRD4 and DOT1L have generally been best characterized in the MLL-FP leukemias, emerging evidence suggests that therapies against these targets may play a role in other molecular subsets of acute leukemia and indeed other malignancies [46][47][48][49] . The differential sensitivity to these therapies in other cancers is presumably the result of intrinsic differences in the molecular pathogenesis of these diseases as well as the existence of several other protein complexes that lack DOT1L or BRD4 and affect or regulate malignant transcription programs initiated by non-MLL-FP oncogenes 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…DOT1L inhibitors have been developed and are currently in clinical trials for the treatment of MLL-r leukemia (Stein and Tallman, 2015). DOT1L has also been implicated in other cancers, and it has a role in normal development and cellular reprogramming (reviewed in McLean et al (2014) and Nguyen and Zhang (2011)). Furthermore, Dot1 plays a role in meiotic checkpoint activation and the DNA damage response (Nguyen and Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT3A mutants may play a role in up-regulating HOX genes in AML. Novel H3-methyltransferase inhibitors such as DOT1L inhibitors (McLean et al 2014), MLLmenin interaction inhibitors (Borkin et al 2015), and MLL inhibitors (Cao et al 2014) showed efficient knockdown of HOX cluster genes and leukemic cell death, both in vitro and in vivo. Although these compounds were mainly tested in the context of MLL-rearranged leukemia, a wider spectrum of leukemias, including DNMT3A mut AML, may be sensitive to this treatment.…”
Section: Therapeutic Perspectives and Future Directionsmentioning
confidence: 99%